2011
DOI: 10.1002/dev.20590
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical and behavioral measures of response monitoring in young children during a Go/No‐Go task

Abstract: The current study examined behavioral measures and response-locked event-related brain potentials (ERPs) derived from a Go/No-Go task in a large (N = 328) sample of 5- to 7-year-olds in order to better understand the early development of response monitoring and the impact of child age and sex. In particular, the error-related negativity (ERN, defined on both error trials alone and the difference between error and correct trials, or ΔERN), correct response negativity (CRN), and error positivity (Pe) were examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
101
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 95 publications
(131 citation statements)
references
References 70 publications
27
101
3
Order By: Relevance
“…While several other studies utilizing similar task designs have examined ERN (Torpey et al, 2012, 2009), we were unable to do so in this study because the children made few errors. However, analyzing ERN could potentially give us additional insights into the development of response inhibition abilities in early childhood and future studies should undertake such an investigation.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…While several other studies utilizing similar task designs have examined ERN (Torpey et al, 2012, 2009), we were unable to do so in this study because the children made few errors. However, analyzing ERN could potentially give us additional insights into the development of response inhibition abilities in early childhood and future studies should undertake such an investigation.…”
Section: Discussionmentioning
confidence: 92%
“…Adopting a similar paradigm, another study with 5–6 year-olds reported that better response inhibition performance during negative emotional induction was accompanied by greater EEG power in the theta frequency range, though no differences in the N2 amplitude were seen (Farbiash & Berger, 2015). Several other studies have also incorporated EEG with the GNG paradigm to examine brain activity related to error detection and monitoring in 5 to 7-year-old children (Torpey, Hajcak, Kim, Kujawa, & Klein, 2012; Torpey, Hajcak, & Klein, 2009). These studies, however, did not look at the neural correlates associated with response inhibition in early childhood.…”
mentioning
confidence: 99%
“…Since the response-locked error-related negativity and correct-related negativity and stimulus-locked N100 components were maximal at the Cz and Fz electrodes, respectively, measurements of amplitude from these electrodes were used in the analyses. In line with previous published findings 28 we were interested in examining the degree of error-related negativity/correct-related negativity and N100 activation. Therefore, we focused on amplitude measurements.…”
Section: Electrophysiology Recordingsmentioning
confidence: 86%
“…Brain event-related potential (ERP) studies have identified the ERN as a robust marker of anterior cingulate cortex-mediated cognitive control processes invoked by performance errors (Holroyd & Coles, 2002;Yeung, Botvinick, & Cohen, 2004). The ERN is clearly evident in adolescents as well as adults (Davies, Segalowitz, & Gavin, 2004) and, more recently, has been observed in young children (i.e., ages 5-11; Kim, Iwaki, Imashioya, Uno, & Fujita, 2007;Torpey, Hajcak, Kim, Kujawa, & Klein, 2012;Wiersema, van der Meere, & Roeyers, 2007). The ERN thus represents a neurophysiological marker of cognitive control across development.…”
Section: Clinical Feasibility Of Measuring Neurobehavioral Constructsmentioning
confidence: 96%